(untitled) (Education in the 21st Century, 2023)
In 1989, the author co-founded, at the UK’s University of Manchester, the first Research Centre for Formative Assessment Studies (CFAS). The aim of the original Research Centre was to investigate and evidence accessible learner-centred models and methodologies of formative teaching and learning that would make both those processes more effective for all learners. The impetus for this current Literature Review is based on the researchers’ previous work on formative pedagogical models and related curriculum development observations and analysis of the implementation and effect of the current surge in interest in ‘transformative pedagogy’. At a cursory reading, this Literature Review, 34 years after the commencement of the original Research Centre’s work, indicates, in global research terms, how difficult the intervening years have been in integrating that formative model of transactional teaching and learning into common usage. A major issue has been the dominance at international policy-level of the model of ‘high stakes’ summative testing or the accretion (‘farming’) of low-level, whole cohort data as a ‘quick and dirty’ measure of student performance, teacher effectiveness and institutional performance. The literature on the fallacy of that model is voluminous but the defensive, fall-back position taken by international Education Ministries is usually ‘parents expect to see Grades and would be disappointed if we did not maintain that model’.